Evaluation Of The Implementation, Collection, Recording, And Reporting Of Income Tax On The Procurement Of Goods In Military Courts III – 17 Manado - Robby Irsyad Bisyir; Treesje Runtu; Meily Y. B. Kalalo (Universitas Sam Ratulangi, 2022)
Military Court III – 17 Manado is one of the state institutions engaged in the courts to provide appropriate punishments for the negligence or disobedience of a military officer in acting outside or inside his job. From the main function of the Military Court III – 17 Manado, there are many questions regarding what needs or availability must be met so that the system and workforce can maintain their performance. And from the existence of these needs, there must always be materials or goods needed. In the procurement of goods, the tax that will be imposed according to the applicable law for the procurement of goods is Income Tax Article 22 regarding purchases made with State Revenue and Expenditure Budget funds. With the many activities carried out by the Manado Military Court III – 17, suspicions arose over the obligatory solicitations related to the procurement of goods. Therefore, the evaluation of the implementation was carried out to test the responsibility of the Military Court III-17 Manado in proving that taxpayers were carried out optimally. The analytical method used is a descriptive method that describes or describes the data that has been collected based on the results of direct interviews at the Military Court III-17 Manado. This is the basis and evidence for the evaluation of Income Tax on the procurement of goods at the Military Court III – 17 Manado.